Does industry type matter?. Sustainability reporting disclosure gaps between manufacturing and non-manufacturing firms - Yatim, Muhammad Rubiul; Al Islami, Muhammad Izzah; Wahyudi, Ade; Indriati, Petiana; Azizah, Widyaningsih (Universitas Pamulang, 2024)
This study examines the differences in the level of sustainability report disclosures between manufacturing and non-manufacturing companies listed on the Indonesia Stock Exchange in 2022. Using GRI standards, the analysis was conducted on 699 companies selected through purposive sampling. The Mann-Whitney test results show that manufacturing companies have higher levels of sustainability disclosure compared to non-manufacturing companies. This research is significant as it addresses the global demand for corporate accountability in sustainability, particularly in Indonesia, where disclosure quality varies across sectors. The findings emphasize that stakeholder and regulatory pressures play a critical role in promoting sustainability practices, consistent with Stakeholder Theory and Legitimacy Theory. The implications of this study highlight the need for stricter regulatory policies to encourage sustainability disclosures across all sectors. Non-manufacturing companies can leverage these findings to enhance their reputation and competitiveness through the adoption of sustainability practices. This study provides strategic insights for regulators, companies, and the public to strengthen sustainability agendas comprehensively.